(untitled) (Revista Latino-Americana de Enfermagem, 2003)
The purpose of this study was to assess the elements of respiratory mechanics in obese individuals with respect to respiratory muscle strength determined by maximum respiratory pressure (PImax and PEmax) and the amplitude of thoracoabdominal movements at the levels: axillary (AAX), xiphoid (AXf) and abdominal (AAb).Twenty nine patients (43 ± 13 years) were divided in two groups: Experimental group (E) and Control group (C). All patients were submitted to an initial evaluation and determination of PImax, PEmax, AAx, AXiph and AAb. The E group was submitted to 18 sessions of a Functional Reeducation of Breathing Program that consisted of respiratory orientation, respiratory coordination exercise associated to trunk and limb movements and muscle relaxation two times a week during 9 weeks. Student t-test showed a significant increase in PImax, Axif and Aabd in the experimental group, but when authors compared the two groups, they did not find any statistical difference. The results showed that the Program increased the respiratory muscle strength and the amplitude of abdominal movements in obese patients.